2017
DOI: 10.1111/jopr.12648
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Increased Concavity of Maxillary Labial Alveolar Bone and Decreased Labial Cortical Bone Thickness: A Cone Beam Computed Tomography Aided Retrospective Cohort Study

Abstract: According to the results of this study an increased maxillary labial concavity was associated with reduced thickness of the labial cortical wall and the presence of a horizontal groove at the philtrum area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 18 publications
1
13
1
Order By: Relevance
“…9,30 In this study, the maxillary central incisors had smaller concavity angles (131.6° and 131.9°), and the canines had larger concavity angles (139.4° and 139.7°). The results of this study are similar to those reported by Calvani et al 18 who indicated that the concavity angles of the central incisors were the smallest (130.4° and 129.6°) and those of the canines were the largest (141.2° and 140.8°; Table 6). The central incisors had a small concavity angle, indicating that this area had a low risk of alveolar bone perforation.…”
Section: Comparison Psupporting
confidence: 91%
See 3 more Smart Citations
“…9,30 In this study, the maxillary central incisors had smaller concavity angles (131.6° and 131.9°), and the canines had larger concavity angles (139.4° and 139.7°). The results of this study are similar to those reported by Calvani et al 18 who indicated that the concavity angles of the central incisors were the smallest (130.4° and 129.6°) and those of the canines were the largest (141.2° and 140.8°; Table 6). The central incisors had a small concavity angle, indicating that this area had a low risk of alveolar bone perforation.…”
Section: Comparison Psupporting
confidence: 91%
“…23 The risk of the alveolar cortical bone undergoing iatrogenic perforation by the implant increases when the alveolar bone concavity angle is larger. 15,18 Therefore, gaining an understanding of the SRP and alveolar bone concavity can help reduce surgical complications, prevent labial bone perforation, determine suitable implant diameter and length, and provide anatomical information to guide implant placement in the optimal position, especially in the case of immediate implant placement in the maxillary teeth. 24 CBCT can provide detailed volumetric image data of the maxillofacial area, can present the complete geometric shape of the area of interest, and prevent the superimposition or planar views, thus enabling accurate radiographic interpretation A paired T test was performed to compare measurements between the maxillary right and left central incisors, between the maxillary right and left lateral incisors, and between the maxillary right and left canines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some articles were excluded after full-text review for the following reasons: Lack of data referring to BBT [ 65 , 66 , 67 , 68 ], measurement not by (CB)CT scan [ 69 ] patients matching the exclusion criteria [ 19 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ], patients with implants [ 85 ], patients without teeth [ 86 ], data not displayed as mean and SD [ 56 ], site or kind of measurement not adequate [ 19 , 62 , 64 , 77 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ,…”
Section: Resultsmentioning
confidence: 99%